Sejarah Perkembangan STAI Ali bin Abi Thalib di Surabaya 1996-2016 M - Ari Dwi Putra Wardana (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2018)
Abstract: Research on this article aims to determine private Islamic colleges in the northern region of Surabaya. Some limitations of research on this problem are: (1). What is the history of the establishment of STAI Ali Bin Abi Talib in Surabaya (2). How is the dynamics of its development in Surabaya in 2006-2016 (3). What are the supporting and inhibiting factors in its development. This article is written using historical research methods, namely heuristics, verification, interpretation and historiography. The approach used is a historical approach with a diachronic perspective (describing events that occurred in the past chronologically in the time dimension). While the theory used to analyze is the theory of sociology, namely John Obert Voll; Continuity and Change, (continuity and change) and Arnold J. Toynbee; Challenges and Responses (challenges and responses). From the results of the research conducted, it can be concluded that: (1) STAI Ali Bin Abi Talib was founded in 2007 AD in the Sidotopo Kidul 51 area of ​​Surabaya. -1996 M Al Irsyad organization, East Java. (2) STAI Ali Bin Abi Talib has experienced growth from the number of facilities and infrastructure in the first period of around 10 rooms to now reaching 18 rooms. The teachers of STAI Ali Bin Abi Talib experienced an increase in quality over time, namely 7 graduates of Postgraduate and Masters degrees. (3) the supporting and inhibiting factors for STAI Ali Bin Abi Talib are divided into two factors, namely internal factors and external factors. Keywords: Al Irsyad, high school, internal factor, external factor